Signs And Connotative Meanings of Korean Drama Scenes â€œStart Upâ€ - Duwila, shanty (Faculty of Letters, Universitas Dr. Soetomo, Surabaya, Indonesia, 2024)
One of the most popular Korean drama series today is â€œStart Up.â€ This drama becomes popular as it has motivated viewers to explore entrepreneurship. There are some signs and symbols in this drama implying valuable messages for its viewers. This present study applies Roland Barthesâ€™s semiotics theory to find out types of connotative signs and their meaning. The data are scenes from portrayal life of Seo Dalmi and Nam Dosan. Using qualitative descriptive methods, the procedures of data collection and data analysis are: 1) selecting the scene in the Korean drama